Enhancement of capacity in applied biometry in East and southern Africa - Rowlands, G.J. (International Livestock Research Institute, 2000)
Biometric skills in developing countries are inadequate to support the changing priorities of agricultural research with the consequence that the quality of research aimed at increasing food security and alleviating poverty is often deficient because it lacks good statistical design" (CTA, 1997). It was on this basis that the workshop was planned, realising that not only do national scientists and statisticians (biometricians) need training in applied biometrics but they also need to be exposed to the range of problems and complexity of agricultural study design necessary for the developing world. Few courses in applied biometrics exist in universities in East and southern Africa. Training in biometrics provided hitherto by overseas institutions has been beneficial, but lecturers do not often have a full appreciation, or practical hands-on experience, of the special features of agricultural research and development in Africa. The subjects of experimental design, statistical analysis, interpretation and presentation of results are still recognised to be among the top priorities for training by national agricultural research system (NARS) scientists participating in collaborative networks co-ordinated by the International Livestock Research Institute (ILRI) and the International Centre for Research in Agroforestry (ICRAF). There is thus a major need to establish strong training programmes in the region itself with links to existing programmes abroad.